Veterinarians and impostor syndrome: an exploratory study. (22nd June 2020) - Kogan, Lori R; Schoenfeld‐Tacher, Regina; Hellyer, Peter; Grigg, Emma K; Kramer, Emily
Abstract : Background: Impostor syndrome (IS) is the tendency to doubt one's abilities despite positive evidence to the contrary. Individuals with IS are afraid of being discovered as intellectual frauds and attribute their successes to external qualities. Methods: An international study explored the prevalence and severity of IS in practicing veterinarians. An anonymous survey consisting of the 20‐question Clance Impostor Phenomenon Scale, plus additional demographic and work‐related questions, was distributed online. Results: A total of 941 practicing veterinarians responded. Overall, 631 participants (68 per cent) met or exceeded the clinical cut‐off score for IS. Ordinal regressions found that residing in New Zealand (NZ) or the UK, being female or having been in practice for less than five years increased the odds of having a high IS score. The effect of these factors on the perceived degree of impact of IS on participants' professional and personal life was also explored. Women, UK residents and new practitioners reported higher levels of impact in their professional life. However, sex and country of residence did not affect the degree of impact on participants' personal life. Conclusion: Veterinarians in general have an alarmingly high prevalence of IS with young, female graduates practising in the UK and NZ at increased risk.